Ruptured Cavernoma Associated with Developmental Venous Anomaly: Case Report - Nogarotto Cembraneli, Pedro; Brasileiro de Faria Cavalcante, Julia; Nogarotto Cembraneli, Italo; Brasileiro de Faria Cavalcante, Renata; da Silva Cavalcante, José Edison; Taveira Lopes, Leonardo; Fonseca Cardoso, Alessandro; Antônio Zanini , Marco; Fonseca Cardoso, Chrystiano (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Cerebral Cavernous Malformations (CCMs) are rare vascular lesions, often associated with genetic mutations. The association between these malformations and Developmental Venous Anomaly (DVA) has been the focus of recent studies, as they may influence the evolution of the lesions. Case Presentation: A 26-year-old female patient presented with a sudden onset of severe headache, vertigo, and ataxia, requiring hospitalization due to cerebellar hemorrhage confirmed by CT scan. Magnetic Resonance Imaging (MRI) revealed a cavernoma in the right cerebellar peduncle with an adjacent DVA. The patient underwent surgical intervention with intraoperative neuronavigation, where the DVA was used as an anatomical landmark to locate and completely excise the cavernoma while preserving the anomalous vein. Postoperatively, the patient showed significant improvement without neurological deficits. Conclusion: CCMs can be sporadic or familial, and they are frequently associated with DVAs. DVA resection can impair venous drainage and cause infarction, making its preservation crucial during surgery. A conservative approach is recommended in most cases, with resection indicated for symptomatic lesions or those at high risk of bleeding.